Gaussian extended cubature formulae for polyharmonic functions - Bojanov, Borislav D.; Dimitrov, Dimitar K. [UNESP] (American Mathematical Society (AMS), 2001)
The purpose of this paper is to show certain links between univariate interpolation by algebraic polynomials and the representation of polyharmonic functions. This allows us to construct cubature formulae for multivariate functions having highest order of precision with respect to the class of polyharmonic functions. We obtain a Gauss type cubature formula that uses ℳ values of linear functional (integrals over hyperspheres) and is exact for all 2ℳ-harmonic functions, and consequently, for all algebraic polynomials of n variables of degree 4ℳ - 1.
Keywords: Extended cubature formula; Gaussian extended cubature formula; Polyharmonic function; Polyharmonic order of precision